Do whale-watching experiences and tourist expectations align? A comparison of three Macaronesian destinations - Claudia Hurtado-Pampín; Raquel de la Cruz-Modino; David Domínguez-González; Álvaro Herrera-Cáceres; Sara Vicente-Alonso; Patricia Arranz (PLoS ONE, 2026)
This study examines the alignment between whale-watching experiences and tourist expectations in three different destinations. Whale-watching is a global tourist activity, with locations such as the Canary Islands (Spain) and the Azores (Portugal) in Macaronesia rapidly becoming prime spots for these marine activities. Those locations attract a significant number of tourists with varying recreational interests and diverse perceptions of each destination and its natural resources, including marine wildlife megafauna species that can be seen. While often marketed as sustainable tourism, the ecological impacts of whale-watching are a matter of concern. Evolving whale-watching practices may reinforce or diminish the effectiveness of conservation and environmental education efforts. In this regard, exploring whale watchers’ expectatives, preferences, previous experiences, level of satisfaction, and environmental information may help to assess better practices and sustainable tourism initiatives. This study employed a multidisciplinary approach, incorporating a series of questionnaires that explored whale watchers’ expectations and overall satisfaction before and after sea trips in the Tenerife and El Hierro Islands (Canary Islands, Spain), as well as in São Miguel (Azores, Portugal). The findings highlight differences across three study cases: El Hierro attracted more experienced and oriented tourists, while Tenerife and São Miguel received more generalist visitors. Satisfaction was closely linked to the number of cetacean sightings. Many participants who did not mention specific species expressed open preferences such as wanting to “see everything” or “whatever is possible”, reflecting limited prior knowledge. The study highlights the importance of tailoring whale-watching strategies to tourist profiles by enhancing communication, adjusting group sizes and vessel types, and reinforcing conservation messaging to ensure both positive experiences and long-term ecological sustainability.